mTOR inhibitors: optimizing outcomes and expectations in complex vascular anomalies. - Johnson, L.; Woo, R.K.; Puapong, D.P.; Jensen, J.; Spence-Shishido, A.; O'Donnell , P.J.; Lewis, S.; Johnson, S.M. (European Journal of Pediatric Dermatology, 2026)
Just as propranolol has transformed the treatment of infantile hemangiomas, mTOR inhibitors have become significant targeted therapies for non-involuting and complex vascular malformations — such as lymphatic and the PIK3CA-related malformations. This retrospective cohort study reviewed 30 patients treated with mTOR inhibitors at Kapiolani Medical Center’s Vascular Anomalies Center (2017-2023). Included were venous malformations (VM), lymphatic malformations (LM), capillary malformations (CM), and combined malformations. Data collected included demographics, lesion characteristics, treatment duration, adverse effects, and adjunctive therapies. Treatment response was graded using a five-point scale (1=no response, 5=near-complete resolution). Patients ranged from 4 months to 23 years of age (mean: 11 years of age) with treatment durations of 2 weeks to 6 years (mean: 24.2 months). Lesions were predominantly located on limbs (63.3%), face/neck (30%), and trunk (30%). PROS malformations (20%, n=6) showed moderate to dramatic improvements (mean treatment response score 3.3), whereas non-PROS malformations (80%, n=24), including VM, LM, CM, and isolated combined malformations, had milder responses (mean treatment response score 1.8). Over 50% of all patients required adjunct therapies, including embolization, sclerosis, debulking, or additional medications. Adverse effects (40%) included pain, oral ulcers, and viral illnesses, with no severe complications. mTOR inhibitors offer symptom relief for vascular malformations in general, with more pronounced effects in syndromic combined malformations, such as PROS-related KTS. Pediatric dermatologists should consider mTOR therapy for cutaneous symptoms like swelling, bleeding vesicles, and microlymphatic lesions. Multimodal approaches, including sclerotherapy and debulking, remain essential for both lesion types.